The Role Of Corporate Governance In Enhancing E-Marketing : Study At Rashid Bank Palestine Street Branch. - Asst. lecture .Hassan D Obaid (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study examines the effective role played by corporate governance in promoting e-marketing strategies, through an applied study conducted on Al-Rasheed Bank - Palestine Street Branch. In light of the rapid developments in the digital field, organizations are increasingly relying on e-marketing tools to improve their performance, making it necessary to apply governance principles to ensure the highest levels of efficiency, transparency, and credibility. The study aims to illustrate how governance can contribute to improving the performance of e-marketing in financial institutions, With a focus on Al-Rasheed Bank as an applied model. The study seeks to achieve several objectives, including analyzing the impact of governance mechanisms on e-marketing strategies, and knowing the extent to which the application of governance is related to achieving institutional goals and improving marketing efficiency. It also aims to study how governance contributes to building a transparent and secure relationship between the organization and its customers, which enhances loyalty and expands the customer base. In addition, the study highlights the challenges that organizations may face in applying governance to e-marketing and proposes solutions to address them. The study showed that there is a strong relationship between corporate governance and e-marketing, as governance helps in defining the goals and vision of the organization, which ensures that e-marketing strategies are compatible with the general directions of the organization. Enhancing transparency and accountability also contributes to building customers' trust in the organization, which increases their positive interaction with its marketing strategies. Moreover, governance helps ensure compliance with legal and ethical standards, which enhances the organization's reputation in the market and reduces the legal risks it may face. The study relied on the descriptive and analytical approach to analyze the relationship between governance and e-marketing, with a focus on data related to Al-Rasheed Bank - Palestine Street Branch. A simple random sample of 50 employees from different departments within the bank was selected. Statistical analysis was also used to measure the impact of governance on the efficiency of e-marketing within the organization. The results of the study showed that 84% of employees believe that corporate governance plays a key role in the success of digital marketing campaigns, reflecting a broad awareness of the importance of regulatory frameworks and corporate policies in guiding digital marketing operations. 73% of employees also confirmed that there are clear governance policies within the bank, which enhances confidence in the corporate system. With regard to customer trust, 79% of employees indicated that governance contributes to improving the level of trust in the electronic services provided by the bank, while 73% of them believe that governance positively affects the process of strategic decision-making in e-marketing. Also, 71% of employees reported that there is an effective system to monitor the performance of digital marketing campaigns, which helps to evaluate performance and improve strategies based on the results achieved. However, the study noted that there are some challenges facing the implementation of governance in the field of e-marketing. 33% of employees indicated that there is a lack of regular training programs on governance practices, which may negatively affect the effectiveness of their implementation. 38% of respondents also showed weakness in the mechanisms for evaluating the effectiveness of governance in improving e-marketing. In addition, 45% of employees indicated that there are gaps in communication between the governance department and the e-marketing department, which calls for improving channels Communication to ensure the integration of efforts between different departments. Based on these results, the study provided a set of recommendations aimed at improving the application of governance in e-marketing. Among these recommendations is the need to organize training workshops to familiarize employees with governance practices and their importance in improving marketing performance. The study also recommended the use of key performance indicators (KPIs) to conduct periodic evaluations and improve marketing strategies based on the results of these evaluations. In addition, the study stressed the importance of strengthening coordination between governance and e-marketing departments to ensure the integration of efforts and achieve Better results. It also recommended updating governance policies to keep pace with developments in the field of e-marketing, in order to contribute to supporting innovation and creativity in digital marketing strategies. In conclusion, the study confirmed that corporate governance plays a vital role in improving the efficiency of e-marketing, which contributes to enhancing customer confidence, achieving regulatory compliance, and increasing the effectiveness of marketing campaigns in financial institutions, especially in Rasheed Bank. She also stressed the importance of developing periodic training and evaluation strategies to ensure the optimal application of governance principles, in a way that enhances the performance of institutions in the changing digital environment.